Set Dekorasi dengan Komposisi Obvious Balance dalam Program Variety Show - Willhelmus Filianto; Sigit Winarso; Septia Ningrum (Journal on Education, 2023)
Now days many entertaining program with show format is exist in Indonesian television program. The variety performance of the artist with beauty visualization created by lighting design make sets and staging just like an ordinary music concert’s stage. Art director have a complex job, more than build the set and stage. Art director should have a concept for television’s program. The concept expressed through element of design such as line, color, and composition of balance from the set decoration. With that concept the set decoration have aesthetic look and have meaning inside. To insert meaning on the element of set decoration it need to get many information from observe and literature review. So the information can support the meaning in design as well. Set decoration of variety show “Inklusi” is a creation that consist obvious balance concept in it. This concept has made by the hottest issue in Inklusi program. Through the set decoration, author make set and stage that speaks up for difabel, to be equal with others.